Pengaruh Kevakuman Jabatan Majelis Pengawas Wilayah Notaris terhadap Efektivitas Pembinaan dan Pengawasan Notaris di Aceh - Suhaimi, Suhaimi; MH, Nurdin; Tinianus, Enzus (Prodi Ilmu Hukum, Universitas Teuku Umar, 2023)
Article 72 of Law No.30 of 2004 concerning to the Position of a Notary, as amended by Law Number 2 of 2014 concerning to Amendments to Law No.30 of 2004 concerning to the position of a Notary (hereinafter referred to as the Law on Notary Position and abbreviated as UUJN), states that the duration of position for the Notary Regional Supervisory Council (MPWN) are 3 (three) years, but the duration of notary for the Aceh MPWN, which on 27 September 2020 has alredy turned 3 (three) years, turns out that until 19 May 2021 there has been no replacement for a new MPWN. As a result, there has been a vacuum in the Aceh MPWN for 7.2 months. So it would be interesting if a scientific study was carried out on the effect of the MPWN's vacuum on the effectiveness of the guidance and supervision of Notaries in Aceh. This type of research is included in empirical legal research. The primary data was obtained through field research, by conducting interviews with respondents and several informants. The results of the study revealed that when the Aceh MPWN was vacuumed, there were 2 (two) MPDN recommendations with 2 (two) Notaries indicating violations of the UUJN and/or the Notary Code of Ethics, namely the MPDN for Banda Aceh Municipality and Aceh Besar District. However, due to the vacuum of the Aceh MPWN and its members having been retired, the Aceh MPWN is not authorized to handle and follow up on the recommendations of the two MPDN. The legal consequence is that the guidance and supervision of Notaries is not carried out effectively.